Analisis Pengembangan Wilayah Berbasis Potensi Unggul Daerah Melalui Tata Kelola Ekonomi Daerah Kota Semarang - Ranti Astari Rahayu; Irfan Ferdiansyah; Rika Dinda Lestar; Priskila Priskila; Asthevania Dhara Monika; Noer Apptika Fujilestari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The research carried out has the aim of understanding regional development based on regional superior capabilities through regional economic management in Semarang City. Urban development always involves increasing the built-up area. On the other hand, the increase in population and commercial activities as well as limited urban areas have made efficient use of land a necessity that cannot be ignored. A set of urban development efforts such as residential areas, in regional development there are industrial and highway networks, drinking water networks and public buildings, green areas & facilities. The city of Semarang, as the economic center and capital of Central Java, provides regional development opportunities beyond other cities in Central Asia by implementing specific development strategies based on its regional potential. Data was collected through library surveys without requiring a field survey, but with data from books and periodicals. Based on research findings, Semarang has the potential to experience population growth, increasingly advanced science and technology, as well as economic development due to its maritime, tourism, trade, social, economic and cultural wealth.